Examination of pyroelectric power generation over a wide temperature range by controlling the Zr:Sn composition ratio of PLZST. Issue 1 (2nd January 2022) - Sugiyama, Hironari; Kim, Juyong; Yamanaka, Satoru; Kim, Yoonho; Ngo, Nguyen Chi Trung; Wiff, Juan Paulo; Suzuki, Tsuneo; Baba, Masaaki; Takeda, Masatoshi; Yamada, Noboru; Sekino, Tohru; Hashimoto, Hideki; et al.
ABSTRACT: Several studies have been conducted on energy harvesting, which involves conversion of unused environmental energy into a power source. More than half of the energy consumed is wasted as heat. Therefore, attempts are being made to increase energy efficiency by effectively utilizing the waste heat as renewable energy. In this study, we focused on the time-varying waste heat source and fabricated lead lanthanum stannate zirconate titanate (PLZST) ceramics, which are pyroelectric materials. The electrical properties and power densities of the PLZSTs with five different compositional ratios of Zr and Sn were evaluated as functions of temperature. As the proportion of Zr increased, both the maximum dielectric constant and the maximum power density at each composition ratio shifted to higher temperatures. By controlling the Zr:Sn ratio in PLZSTs, power densities of more than 8 mW/cm 3 were obtained over a wide temperature range of 140–200°C. In addition, power densities of more than 10 mW/cm 3 were obtained between 150°C and 180°C. Therefore, we observed that PLZST is a promising material for the recovery of power from low-grade heat sources below 200°C.